Pengaruh SBI, SBIS, Inflasi dan Nilai Tukar Rupiah Terhadap Transaksi Pasar Uang Antar Bank Syariah - Nursantri Yanti (Universitas Islam Negeri Sumatera Utara, 2018)
This research aims to determine how much influence SBI, SBIS, Inflation and Exchange Rate to Interbank Islamic Money Market from January 2010 to June 2015. This quantitative research using the analysis of Vector Auto Regressive helped by Eviews version 8. From the results conducted at alpha 5%, the results of VAR analysis Decomposition Variance test showed that the variables SBI, SBIS, Inflation and Exchange Rate affect the Interbank Islamic Money Market. In the short term or the beginning of the observation period SBIS has the most dominant influence among other variables againts Interbank Islamic Money Market.While in the long term or the end of the observation period inflation has the most dominant influence on the Interbank Islamic Money Market. Granger causality test results indicate that all variables have a causal relationship to one another, meaning that each variable has a 2-way relationships with other variables. While the impulse response function test results showed that the Interbank Islamic Money Market, SBI responds very well balanced, responds SBIS with a negative response and more balanced, responds to variable inflation and exchange rate are very balanced. Interbank Islamic money market is more influenced by the instruments in conventional banks namely SBI.